颞下颌关节滑膜软骨瘤病的临床分析 (Nan Fang Yi Ke Da Xue Xue Bao, 2017)
Five patients with synovial chondromatosis in the temporomandibular joint were treated in our hospital between August, 2011 and August, 2014. All the patients underwent preoperative imaging examinations for clinical diagnosis and determining the involvement of the lesions. Surgeries were performed and the lesions were confirmed as synovial chondromatosis by pathological diagnosis. The clinical manifestations, imaging features, diagnosis and treatment results were analyzed. All the 5 patients had pain in the joint region, 3 had limited mouth opening, and 3 had swelling in the joint region. X-ray film showed widening of the joint space in all the 5 cases and radiographic findings showed space-occupying lesions in the intra-articular space. Open joint surgeries was performed and completed successfully in all the cases. The postoperative imaging showed no residual lesions in the surgical area. As a rare clinical entity, synovial chondromatosis in the temporomandibular joint was poorly documented without specific clinical manifestations. The diagnosis of synovial chondromatosis relies on imaging, arthroscopic and pathological findings. Corpus liberum is an important feature of the disease occurring frequently in the joint cavity. Surgical intervention is the primary choice for treatment of synovial chondromatosis in the temporomandibular joint, in which the corpus liberum and the affected synovial membrane shall be removed after joint incision.